Subways, Strikes, and Slowdowns: The Impacts of Public Transit on Traffic Congestion - Anderson, Michael L. (American Economic Review, 2014)
Public transit accounts for 1 percent of US passenger miles traveled but attracts strong public support. Using a simple choice model, we predict that transit riders are likely to be individuals who commute along routes with severe roadway delays. These individuals' choices thus have high marginal impacts on congestion. We test this prediction with data from a strike in 2003 by Los Angeles transit workers. Estimating a regression discontinuity design, we find that average highway delay increases 47 percent when transit service ceases. We find that the net benefits of transit systems appear to be much larger than previously believed. (JEL H76, J52, L92, R41)